PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ASSURE DALAM MENINGKATKAN HASIL BELAJAR SISWA - Kosilah Kosilah; Septian Septian (Jurnal Inovasi Penelitian, 2020)
The purpose of this study was to determine the increase in student learning outcomes by applying the Assure Type Cooperative Learning Model to students, especially class V SD Negeri 2 Manuru, Buton Regency. Data collection techniques in this study were observation and tests which included observation, documentation and written tests. The results of this study were an increase in student learning outcomes in the material of the Unitary State of the Republic of Indonesia (NKRI) in the PPKn subject through the Assure Type Cooperative Learning Model in grade V SD Negeri 2 Manuru Buton Regency. The percentage of classical completeness before applying the model was only 56%, then classical completeness increased to 68% in cycle I and in cycle II the percentage of classical completeness reached 92%. Thus, it can be concluded that the Assure type of cooperative learning model improves the learning outcomes of fifth grade students of SD Negeri 2 Manuru Buton district in the PPKn subject.